The effect of alcohols on red blood cell mechanical properties and membrane fluidity depends on their molecular size. - Melda Sonmez; Huseyin Yavuz Ince; Ozlem Yalcin; Vladimir Ajdžanović; Ivan Spasojević; Herbert J Meiselman; Oguz K Baskurt (PLoS ONE, 2013)
The role of membrane fluidity in determining red blood cell (RBC) deformability has been suggested by a number of studies. The present investigation evaluated alterations of RBC membrane fluidity, deformability and stability in the presence of four linear alcohols (methanol, ethanol, propanol and butanol) using ektacytometry and electron paramagnetic resonance (EPR) spectroscopy. All alcohols had a biphasic effect on deformability such that it increased then decreased with increasing concentration; the critical concentration for reversal was an inverse function of molecular size. EPR results showed biphasic changes of near-surface fluidity (i.e., increase then decrease) and a decreased fluidity of the lipid core; rank order of effectiveness was butanol > propanol > ethanol > methanol, with a significant correlation between near-surface fluidity and deformability (r = 0.697; p<0.01). The presence of alcohol enhanced the impairment of RBC deformability caused by subjecting cells to 100 Pa shear stress for 300 s, with significant differences from control being observed at higher concentrations of all four alcohols. The level of hemolysis was dependent on molecular size and concentration, whereas echinocytic shape transformation (i.e., biconcave disc to crenated morphology) was observed only for ethanol and propanol. These results are in accordance with available data obtained on model membranes. They document the presence of mechanical links between RBC deformability and near-surface membrane fluidity, chain length-dependence of the ability of alcohols to alter RBC mechanical behavior, and the biphasic response of RBC deformability and near-surface membrane fluidity to increasing alcohol concentrations.